2012
DOI: 10.1002/jbmr.1732
|View full text |Cite
|
Sign up to set email alerts
|

Disease modification of breast cancer–induced bone remodeling by cannabinoid 2 receptor agonists

Abstract: Most commonly originating from breast malignancies, metastatic bone cancer causes bone destruction and severe pain. Although novel chemotherapeutic agents have increased life expectancy, patients are experiencing higher incidences of fracture, pain, and drug-induced side effects; furthermore, recent findings suggest that patients are severely undertreated for their cancer pain. Strong analgesics, namely opiates, are first-line therapy in alleviating cancer-related pain despite the severe side effects, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 79 publications
(135 reference statements)
6
81
1
10
Order By: Relevance
“…These effects of CB2 agonists were prevented by selective CB2 antagonists (4). In other reports, treatment with CB2 agonists suppressed carrageenan-evoked thermal and mechanical hyperalgesia in rodents (12,30,55) and cancer-induced pain (43)(44). Little is known about the effects of CB2 activation on visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…These effects of CB2 agonists were prevented by selective CB2 antagonists (4). In other reports, treatment with CB2 agonists suppressed carrageenan-evoked thermal and mechanical hyperalgesia in rodents (12,30,55) and cancer-induced pain (43)(44). Little is known about the effects of CB2 activation on visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of JWH-015 and AM1241 attenuated tumor-evoked tactile allodynia and thermal hyperalgesia by reducing NR2B-dependent activity [98-99]. CB2 agonist, JWH-015 reduced breast cancer induced bone pain, bone loss, and breast cancer cell proliferation via cytokine/chemokine suppression in murine mammary cell line implanted into the femur intramedullary space [100]. JWH-015 increased survival without the major side effects of current therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical studies have shown that cannabinoid receptor agonists exert analgesic and muscle relaxant properties in patients with metastatic pain (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Most recent interest has been focused on the potential role of CB2-selective agonists in the treatment of malignant disease, because these agents (a) lack of adverse psychotropic effects that are associated with CB1-selective ligands (19), (b) exert anti-proliferative effects on different cancer cell lines (20,21), (c) inhibit cancer-induced osteolysis and fractures (22), and (d) reduce bone pain in various preclinical models (22,23). At the present time CB2 agonists are considered to exert these effects by inhibiting tumor cell growth and by suppressing the release of cytokines and chemokines from cancer cells (24). However, the cellular and molecular mechanisms by which CB2 agonists protect against tumor-induced osteolysis remains incompletely understood.…”
mentioning
confidence: 99%